Misje wojskowe Unii Europejskiej w Afryce - Mikhalev, Oleg (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The author discusses EU military missions in Africa carried out within the framework of the Common Foreign and Security Policy. Making reference to five African missions he analyzes the experience generated by these operations and tries to explain to what extent they might have been conducive to further commitment of the EU in crisis management in Africa. In his opinion, in the future the EU will continue to be present in Africa, yet it is hardly to be expected that its missions will qualitatively differ from present operations.